Manajemen Inovasi dalam Penerapan Deep Learning pada Kurikulum Sekolah Dasar - Natalia, Krisma; Pranata, Pranata (Program Studi PGMI, Universitas Al Falah As Sunniyah Kencong Jember, 2025)
This article aims to analyze the role of innovation management in the implementation of deep learning in the primary school curriculum through a literature review. The study examines relevant national and international literature, covering the concepts of deep learning, implementation challenges, and the integration of innovation management within the context of the Kurikulum Merdeka. The findings indicate that the successful implementation of deep learning is strongly influenced by teacher readiness, instructional leadership of school principals, curriculum innovation, professional development of teachers, collaboration among stakeholders, as well as the availability of resources and consistent policy support. Teachers with an open mindset toward innovation, digital literacy, and collaborative skills are able to implement meaningful and reflective learning. Furthermore, the integration of simple technology and the utilization of local resources support adaptive learning practices despite limited facilities. Based on these findings, this article recommends strategies to strengthen innovation management through transformational leadership, the establishment of teacher learning communities, digital technology integration, and cross-stakeholder synergy to enhance deep learning implementation in primary schools. This study contributes by emphasizing innovation management as a key factor in creating a systematic, adaptive, and sustainable learning ecosystem.